Evidence of localized H₂O increases and O₃ recovery in the Antarctic lower stratospheric vortex: MLS observations and BDC variability during late winter to spring - Hian, Jackson Wui Chang; Chee, Fuei Pien; Justin Sentian; Raul R. Cordero; Chel, Maggie Gee Ooi; Yong, Jie Wong (Elsevier, 2025)
We examined the interannual variability in ozone (O3) and water vapor (H2O) in the lower stratospheric vortex over Antarctica using 19 years of measurements (2004–2022) from the Aura Microwave Limb Sounder (MLS). We focused on the period of the southern hemisphere winter (11–20 September), late winter (21–30 September), and spring (1–10 October) because O3 and H2O dynamics show the most variation during these times. We used a low-pass filter to focus on variations lasting 10 days or longer. The Mann Kendall test and regression analysis were employed to identify linear or non-linear trends. Our findings showed that the vortex-average O3 increased at 0.01 ppm yr- 1. In contrast, the vortex-averaged H₂O showed no significant trend, although localized increases in H₂O were significantly obvious across all latitudes. In addition to the well-known effects of the Montreal Protocol, we hypothesize that the localized increase in H₂O is driven by the redistribution of water vapor due to strengthened Brewer-Dobson circulation (BDC) dynamics, characterized by enhanced horizontal transport, which, however, is insufficient to induce significant changes in vortex-averaged H₂O. The observed out-of-phase trend between the vertical and horizontal branches of the BDC serves to validate our BDC speed calculation. These results highlight the complex interplay between dynamics and chemistry in the polar stratosphere, emphasizing that while O₃ recovery continues, localized changes in H₂O do not yet significantly impact the vortex-averaged H₂O levels. Our study provides new insights and observational evidence into the role of BDC dynamics and stratospheric ozone recovery, underscoring the importance of both chemical and dynamic processes in shaping the future evolution of the stratospheric ozone layer.